A new proof of a box-stacking theorem - Grabiec, Mariusz; Saadati, Reza (Tamsui Oxford Journal of Mathematical Sciences)
In this paper, we define generalized quasi-pseudo-metric spaces on an L-semigroup. Moreover, we also attempt to extend Blumenthal's metric spaces in Boolean algebras to quasi-metric-spaces in Stone algebras.